Energy response of EBT3 radiochromic films: implications for dosimetry in kilovoltage range - Eduardo Villarreal‐Barajas, J. (J Appl Clin Med Phys, 2014)
The objective of this study is to evaluate the suitability of recently introduced radiochromic film EBT3 for clinical dosimetry in the kilovoltage (kV) range. For this purpose, a kV X‐ray irradiator, X RAD 320ix in the range 70 to 300 kVp, a clinical [Formula: see text] source, a 6 MV and an 18 MV X‐ray clinical beam from a Varian linear accelerator were calibrated following AAPM dosimetry protocols. EBT3 films from two different EBT3 batches were placed side‐by‐side on the surface of a water phantom; doses from 0.5 to 4 Gy were delivered. Similarly, irradiations were performed for [Formula: see text] and 6 and 18 MV beams in a water‐equivalent phantom. Films were reproducibly placed at the center of a flatbed scanner and 48‐bit RGB scans were obtained both pre‐ and postirradiations. Net optical density (netOD) and response for a given radiation quality relative to [Formula: see text] was determined for each EBT3 film. The netOD of the red color showed reproducible response (within 1%) for both batches when irradiated using the [Formula: see text] source. For a given dose of 1 Gy of kVp X‐ray, the response relative to [Formula: see text] using the three color channels (red, green, and blue) decreases with decrease in kVp, reaching a maximum underresponse of [Formula: see text] for the 70 kVp. A significant underresponse of [Formula: see text] was observed at 300 kVp. Responses of MV X‐ray beams with respect to [Formula: see text] at the 1 Gy dose level showed no statistically significant difference. A relatively small difference in the response was observed between the two EBT3 batches used in this study in the kV X‐ray range. PACS numbers: 87.56.B, 87.57.uq